Emerging Technologies for Diagnosing Alzheimer's Disease Innovating with Care - Boenink, Marianne; van Lente, Harro; Moors, Ellen; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book explores international biomedical research and development on the early diagnosis of Alzheimer's disease. It offers timely, multidisciplinary reflections on the social and ethical issues raised by promises of early diagnostics and asks under which conditions emerging diagnostic technologies can be considered a responsible innovation. The initial chapters in this edited volume provide an overview and a critical discussion of recent developments in biomedical research on Alzheimer's disease. Subsequent contributions explore the values at stake in current practices of dealing with Alzheimer's disease and dementia, both within and outside the biomedical domain. Novel diagnostic technologies for Alzheimer's disease emerge in a complex and shifting field, full of controversies. Innovating with care requires a precise mapping of how concepts, values and responsibilities are filled in through the confrontation of practices. In doing so, the volume offers a practice-based approach of responsible innovation that is also applicable to other fields of innovation. .
Chapter 1. Introduction; Marianne Boenink, Harro van Lente and Ellen Moors -- Part I. Biomedical Research on AD Diagnostics: Background and Trends -- Chapter 2. The Diagnosis and Treatment of Alzheimer's: Are We Being (Ir)responsible?; Peter J. Whitehouse -- Chapter 3. On Short Cuts: The Complexity of Studying the Early Diagnosis and Prevention of Alzheimer's Disease; Annette Leibing -- Chapter 4. Biomarkers for Alzheimer's Disease: Searching for the Missing Link Between Biology and Clinic; Marianne Boenink -- Chapter 5. Care and Responsibility in Building Futures for Alzheimer's Disease Research; Richard Milne and Shirlene Badger -- Part II. Diagnosing Alzheimer's Disease: Current Practices -- Chapter 6. Grey matters. Emergent biomarkers and good Alzheimer's diagnostics; Anna Laura van der Laan -- Chapter 7. Understanding Cognitive Screening Tools: Navigating Uncertainty in Everyday Clinical Practice; Julia Swallowds Responsible Health Technology Assessment; Ellen Moors and Alexander Peine -- Chapter 14. Diagnosing Alzheimer's Disease: How to Innovate with Care; Marianne Boenink, Harro van Lente and Ellen Moors.
Keywords: Social medicine; Human body-Social aspects; Medicine; Geriatric nursing; Health Promotion and Disease Prevention